Effect of Ozone on Filamentous Bulking in a Laboratory Scale Activated Sludge Reactor Using Respirometry and INT-Dehydrogenase Activity - Caravelli, Alejandro Horacio (2006)
Filamentous bulking can be controlled by the addition of oxidant chemical agents such as ozone. To evaluate the ozone effect on activated sludge from a laboratory scale reactor, different techniques were applied: Settleability test, respirometry oxygen uptake rate, and the INT-dehydrogenase activity test carried out both by spectrophotometry DHAa and image analysis DHA. In activated sludge, the respirometric technique and the spectrophotometric DHAa quantified ozone action on the total respiratory activity of flocs; in contrast, the image DHAi test was applied to evaluate the specific action of ozone on filamentous microorganisms. The conditions for application of the INT-dehydrogenase activity test were standardized using pure cultures of a filamentous microorganism Sphaerotilus natans and a floc-forming bacterium Acinetobacter anitratus. For activated sludge with filamentous bulking, ozone doses and treatment times necessary to improve settleability were established. Ozone dose levels and contact times influence the viability of bacteria in flocs and filaments and the finding of appropriate parameters to preserve floc viability and, at the same time, inhibiting filaments is essential to filament control by ozonation.